2011
DOI: 10.1039/c1an15183e
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytical reduction of disulphide bonds in peptides on Ag-loaded nano-TiO2 for subsequent derivatization and determination

Abstract: We reported an alternative strategy to reduce disulphide bonds in peptides with Ag-nanoparticle loaded nano-TiO(2) (Ag/TiO(2)) under UV irradiation. The feasibility of this strategy was adequately demonstrated using the model peptides oxidized glutathione, vasopressin and insulin, which contain various disulphide bonds, as well as by its application to the determination of Cd-induced phytochelatins in Phaeodactylum tricornutum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Plasmonic enhancements and facile charge transfer resulting from the assistance of metallic Ag are proposed to explain the high photocatalytic activity of the AgVO 3 @AgBr@Ag nanostructures. Previous research has demonstrated that the SPR effect of Ag nanoparticles plays a very important role in producing high visible-light photocatalytic activity for the oscillation of surface electrons. Additionally, the rich conduction band (CB) electrons of noble metals can enhance the reducibility of hybrids, resulting in a decreased recombination opportunity of e – –h + . In particular, the excellent conductivity of Ag nanoparticles greatly promotes interfacial charge-transfer kinetics among Ag, AgBr, and AgVO 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmonic enhancements and facile charge transfer resulting from the assistance of metallic Ag are proposed to explain the high photocatalytic activity of the AgVO 3 @AgBr@Ag nanostructures. Previous research has demonstrated that the SPR effect of Ag nanoparticles plays a very important role in producing high visible-light photocatalytic activity for the oscillation of surface electrons. Additionally, the rich conduction band (CB) electrons of noble metals can enhance the reducibility of hybrids, resulting in a decreased recombination opportunity of e – –h + . In particular, the excellent conductivity of Ag nanoparticles greatly promotes interfacial charge-transfer kinetics among Ag, AgBr, and AgVO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…26−28 Additionally, the rich conduction band (CB) electrons of noble metals can enhance the reducibility of hybrids, resulting in a decreased recombination opportunity of e − −h + . 29 In particular, the excellent conductivity of Ag nanoparticles greatly promotes interfacial charge-transfer kinetics among Ag, AgBr, and AgVO 3 . The proposed charge-transfer mechanism for the AgVO 3 @AgBr@ Ag nanobelt heterostructures is illustrated in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…15 Unique coral-like porous SnO 2 hollow architectures synthesized by Liu and coworkers exhibited an enhanced photovoltaic performance due to their larger effective surface area for dye adsorption, light absorption and utilization than a spherical structure. 16 In addition, constructing hetero-junctions by combining semiconductors with noble metals, such as Au, 17 Ag, 18 Pt 19 and Pd, 13,20 or coupling with metal oxides, such as TiO 2 , 21,22 NiO, 23 Fe 2 O 3 , [24][25][26] ZnO, 27 and WO 3 , 28 has also been proved to be a very effective approach to prevent the recombination of electron-hole pairs. 29 The internal electric eld existing in hetero-junctions between the host semiconductor and the co-catalyst facilitates the separation of electron-hole pairs and induces faster carrier migration.…”
Section: Introductionmentioning
confidence: 99%